Pareto-Improving Intergenerational Transfers - Berthold U. Wigger (Center for Economic Studies and ifo Institute (CESifo), 2000)
In the presence of endogenous growth intergenerational transfer from the young to the old reduce per capita income growth and harm future generations. On the other hand, competitive equilibria are inefficient if externalities sustain long-run growth. This paper shows that if individuals retire in the last period of their life, the inefficiency of the market economy can be removed by an investment subsidy without making the current or future generations worse off only if coupled with intergenerational transfers from the young to the old.
Keywords: 330; Intergenerational transfers; externalities; endogenous growth